How do salinity and heavy metal contamination affect Salicornia ramosissima and the Cadmium accumulation capacity? - Pedro, Carmen (2011)
The major aim of this study was to evaluate the capacity of Salicornia ramosissima, a halophyte present in Obidos lagoon (Portugal), on Cadmium (Cd) phytoremediation, when submitted to different salinities and Cd concentrations, for a month. Two Cd concentrations were used to evaluate this capacity and, consequently, the toxic effect of Cd on the plant development. The contamination levels were tested in different salinities (0, 5 and 10), taking into consideration the natural conditions that S. ramosissima is subject in its natural environment. The mortality registered in the end of the experiment, as the growth parameters measured (length and weight), did not showed significantly differences between the treatments, which means were not affected for the salinity or Cd concentrations, neither for the interaction of those two stress factors. However, length elongation and the variation of weight, observed in the end of the experiment, may have been induced by the increase of salinity and Cd concentration. A highest Cd accumulation was detected in the roots of S. ramosissima, compared with the aerial portion. The Cd accumulation in roots decreased with the increase of salinity and Cd concentration, even though statistically there were no significant differences between treatments. In all treatments, a biofilm was form, highlighting treatment salinity 0 x 50 μg Cd.l-1, where microorganisms and, eventually, organic matter (from the plant), suspended revealed a higher Cd amount relatively to the water initial Cd concentrations. The dissolved Cd concentration, detected in the final of the experiment, was in accordance with the initial contamination levels used in this study; however an increase was observed for some treatments, possible as a result of decomposition of organic matter and consequent release of Cd to the water. Salicornia ramosissima is a potential candidate for Cd phytoremediation at salinities close to 0, where development is maximum and, consequently, is Cd accumulation capacity. The optimization of phytoremediation processes by S. ramosissima could turn possible the use of this plant in freshwater ecosystems.